AVAILABILITY AND UTILIZATION OF E-LEARNING TECHNOLOGIES IN SCIENCE EDUCATION PROGRAMMES IN UNIVERSITIES AT OSUN STATE NIGERIA - ABANIKANNDA, Mutahir Oluwafemi; FADELE, Damilola Adeola (Jurnal Tatsqif, 2024)
The study examined the availability and utilization of e-learning technologies in science education programmes in universities in Osun State. This study adopted a descriptive research design and inventories that were applied to collect data. The respondents in the study were sixty lecturers and three hundred students from three universities in Osun State. The collected data were analyzed by using frequency counts, percentages, mean, standard deviation, and t-tests. Findings reveal that the use of e-learning technologies by lecturers to enhance their teaching and learning activities in science education programmes in universities at Osun State is the same as that of students. Both of them have a high proficiency in utilizing e-learning technologies. However, some recommendations are suggested in this research such as free access to relevant materials should be provided at the university as well as the need for training to be more professional users